Fita reagente no diagnóstico de peritonite em pacientes submetidos a diálise peritoneal - Araújo, Eny Sá de (2009)
Rapid diagnosis of peritonitis remains a significant goal in the management of peritoneal dialysis patients. Several attempts to use leukocytes esterase strips to diagnose peritonitis have been described. This study evaluated the usefulness of Multistix® 10 SG, a urine reagent strip, for diagnosis of peritonitis in peritoneal dialysis patients. Reference standard for peritonitis diagnosis was International Society Peritoneal Dialysis ISPD criteria. A hundred-fifty-two peritoneal effluents were obtained from 96 patients maintained on peritoneal dialysis program, in a single renal replacement therapy center. There were 28 suspected patient specimens and 124 asymptomatic one. White cell count, culture and gram stain were obtained from 28 suspected patient specimens and from 35 asymptomatic one. In 89 asymptomatic patient specimens were obtained only white cell count. Reagent strip was used in all specimens. Prevalence of peritonitis in this sample was 18,41 %. Sensibility, specificity, positive predictive value and negative predictive value of the reagent strip for the diagnosis of peritonitis was 92,86 %, 100 %, 100 % and 98,41 %, respectively. Multistix® 10 SG reagent strip is a sensitive, specific and rapid tool for the diagnosis of peritonitis in peritoneal dialysis patients. Widespread use in peritoneal dialysis would aid in the early recognition and treatment of peritonitis.